Artificial Intelligence and Computational Intelligence 4th International Conference, AICI 2012, Chengdu, China, October 26-28, 2012. Proceedings - Lei, Jingsheng; Wang, Fu Lee.; Deng, Hepu.; Miao, Duoqian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This volume proceedings contains revised selected papers from the 4th International Conference on Artificial Intelligence and Computational Intelligence, AICI 2012, held in Chengdu, China, in October 2012. The total of 163 high-quality papers presented were carefully reviewed and selected from 724 submissions. The papers are organized into topical sections on applications of artificial intelligence, applications of computational intelligence, data mining and knowledge discovery, evolution strategy, expert and decision support systems, fuzzy computation, information security, intelligent control, intelligent image processing, intelligent information fusion, intelligent signal processing, machine learning, neural computation, neural networks, particle swarm optimization, and pattern recognition.
Expressive Secondo Performances of a Realtime Person-Computer Ensemble System -- Different-Level Schemes$1 (BEquivalence for Self-Motion Planning of Robot Manipulators -- Grey Incidence Optimization Model Based on Hybrid Differential Evolution Algorithm -- A Data Mining Based Approach to Research the Relationship between Kansei and Usability: A Case Study of Mobile Phones -- Making Use of the Big Data: Next Generation of Algorithm Trading -- Dynamic Causality Analysis on Default Mode Network -- The Canny Edge Detection and Its Improvement -- Multi-modality Medical Image Registration Based on Improved I-alpha Information (SNI) with Gradient -- Design of Smart Home Control System Based on ZigBee and Embedded Web Technology -- Using Gaussian Potential Function for Underdetermined Blind Sources Separation Based on DUET -- A New Balancing Type of Wireless Sensor Network Routing Algorithm -- Development of Portable Gait Analysis System Based on a DSP -- Improved Neural Networks Based Method for Infrared Focal Plane Arrays Nonuniformity Correction -- Images Classifications Based on Color-Texture Feature -- A Synchronization Strengthen RFID Authentication Protocol Based on Key Array -- Study of a Fuzzy Comprehensive Evaluation Problem in Cloud Computing -- Knowledge-Guided Clustering of Large-Scale Time Series under Wavelet Transformation -- A Significance-Driven Framework for Characterizing and Finding Evolving Patterns of News Networks -- Analysis of Association Rule Mining on Quantitative Concept Lattice -- Composite Rough Sets -- Analysis of Requirement and Constrained Model of Inter-Satellite-Link TT&C Scheduling Problem on Navigation Constellation -- NHFCNNC: A New Fuzzy Neural Network Algorithm Based on Matrix and Its Application -- Research of Emergency Logistics Distribution Routing Optimization Based on Simulated Annealing Ant Colony Optimization -- A Spatial Structure Analysis of Candidate Chinese Hyponymy Based on Concept Space -- Prediction of Energy Consumption Based on Grey Model - GM (1,1) -- Fuzzy Decision Making Based on Fuzzy Logic with Contradictory Negation, Opposite Negation and Medium Negation -- An Approach of Affection Thinking Based on Ant Colony Strategy -- Studies on the Covering Rough Set and Its Matrix Description -- Yard Allocation for Outbound Containers Based on the Unified Neutral Theory of Biodiversity and Biogeography -- An Auto-Adapted Method to Generate Pairwise Test Data Set -- The Application of Evolutionary Algorithm in B-Spline Curved Surface Ffitting -- Self-adaptive Optimization for Traffic Flow Model Based on Evolvable Hardware -- An Improved Decision Tree Algorithm Using Rough Set Theory in Clinical Decision Support System -- An AHP-Based Assessment Model for Clinical Diagnosis and Decision -- The Solution of Smart Home Indoor Positioning Based on WiFi -- Modified Cosine Similarity Measure between Intuitionistic Fuzzy Sets -- An Equipment Failure Prediction Accuracy Improvement Method Based on the Gray GM(1,1) Model -- A Group Decision Making Procedure for Selecting Data Warehouse Systems -- An Architecture for Cloud Computing and Human Immunity Based Network Intrusion Detection -- Robust Algorithm for Detection of Copy-Move Forgery in Digital Images Based on Ridgelet Transform -- Function Projective Synchronization and Parameters Identification of Different Hyperchaotic Systems Based on Adaptive Control -- A General Construction for Multi-authority Attribute-Based Encryption -- GIS-Based Urban Land Development Intensity Impact Factors Analysis -- Application of Adaptive Fuzzy Control in the Variable Speed Wind Turbines -- Short-Term Traffic Flow Forecasting Based on Grey Delay Model -- A Novel Color Image Segmentation Method Based on Improved Region Growing -- A Self-adaptive Segmentation Method by Fusion of Multi-color Space Components -- Traffic Vehicle Behavior Prediction Using Hidden Markov Models -- Efficient Visual Tracking by Using LBP Descriptor -- Trilateral Filtering-Based Retinex for Image Enhancement -- Face Recognition Using a Modified Fuzzy Linear Discriminant Analysis Method -- Progressive Image Registration Based on Probability Boosting Tree -- Rapid Image Segmentation Using Color, Texture and Syntactic Visual Features -- Multi-resolution Image Fusion Algorithm Based on Regional Cross Entropy and Regional Priority -- Graph-Cut Optimization for Video Moving Objects Detection with Geodesic Active Contour -- A Video Copy Detection Algorithm Based on Two-Level Features Measure -- Analyzing Feature Selection of Chromatographic Fingerprints for Oil Production Allocation -- Studies on Wheat Pests Image Segmentation Based on Variational Level Set -- Video Quality Assessment Combining Structural Distortion and Human Visual System -- A Novel Ocean Wind Field Estimation Method SAR Images Based -- Research of Decentralized Collaborative Target Tracking Architecture in the Sea Battlefield for the Complex Sensor Networks -- The Application of Intuitionistic Fuzzy MADM Based on Projection Model in Threat Assessment -- Fault Analysis of Condenser Based on RBF Network and D-S Evidence Theory -- Simulation Research on Singularity Detection of Transient Power Disturbance -- CMMB Image Sequences Measurement Based on Computation in High-Dimension Space -- Two-Dimensional Gibbs Phenomenon for Fractional Fourier Series and Its Resolution -- Horizontally UCA DOA Estimation Performance via Spatial Averaging -- Automatic Object Extraction in Nature Scene Based on Visual Saliency and Super Pixels -- Learning a Ground Object Manifold for Interpreting High-Resolution Sensor Image -- Robust Adaptive Beamforming with Null Widening under Quadratic Constraint -- Conceptual Analysis of Chinese Query of the Interrogative Sentence -- Measuring Information Transmission in Izhikevich Neuron -- Color Image Segmentation Using Centroid Neural Network -- Zhang Fractals Yielded via Solving Time-Varying Nonlinear Complex Equations by Discrete-Time Complex-Valued ZD -- Sub-optimal Multiuser Detector Using a Chaotic Neural Network with Decaying Chaotic Noise -- A Formal Method for Testing Reactive System from Symbolic Model -- Study on the Medium and Long Term of Fishery Forecasting Based on Neural Network -- Application of Wavelet Neural Network in the Fault Diagnosis of Turbine Generator Unit -- Density Based Grid Clustering Partition of the Input Space for RBF Neural Network -- Research of the Urban Air Quality Forecast Method Based on Resource Allocation Network -- A Novel Neural Network Approach for Computing Eigen-Pairs of Real Antisymmetric Matrices -- Pavement Distress Image Recognition Based on Multilayer Autoencoders -- MPSO-Based Operational Conditions Optimization in Chemical Process: A Case Study -- Velocity-Free Multi-Objective Particle Swarm Optimizer with Centroid for Wireless Sensor Network Optimization -- The Improved Particle Swarm Optimization Based on Swarm Distribution Characteristics -- An Analysis of Nonlinear Acceleration Coefficients Adjustment for PSO -- Acoustic Sensor Network Node Self-localization Based on Adaptive Particle Swarm Optimization -- Bimodal Biometrics Based on a Two-Stage Test Sample Representation -- Sparse Discriminating Neighborhood Preserving Embedding -- Complex-Matrix-Based Horizontal and Vertical Discriminant Analysis for Feature Fusion -- Segmentation of CAPTCHAs Based on Complex Networks -- A Robust Kernel-Based Fuzzy C-Means Algorithm by Incorporating Suppressed and Magnified Membership for MRI Image Segmentation -- Quantitative and Qualitative Coordination for Multi-robot Systems -- Image Edge Detection Based on Relative Degree of Grey Incidence and Sobel Operator -- Background Modeling from Surveillance Video Using Rank Minimization -- A Complete Set of Pseudo-Zernike Moment Invariants by Image Shape Description.s
Keywords: Computer science; Computer software; Data mining; Artificial intelligence; Computer vision; Optical pattern recognition; Computer Science; Artificial Intelligence (incl. Robotics).; Pattern Recognition; Image Processing and Computer Vision; Data Mining and Knowledge Discovery; Computation by Abstract Devices; Algorithm Analysis and Problem Complexity